Amyloid and tau PET in cerebral amyloid angiopathy-related inflammation two case reports and literature review - Yang, Jhih-Yong; Chu, Yung-Tsai; Tsai, Hsin-Hsi; Jeng, Jiann-Shing (Frontiers in Neurology, 2023)
Background: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is a clinical syndrome characterized by MRI findings of amyloid-related imaging abnormalities-edema (ARIA-E) suggestive of autoimmune and inflammatory reaction and hemorrhagic evidence of cerebral amyloid angiopathy. The longitudinal variation of amyloid PET and its imaging association with CAA-ri are undetermined. Moreover, tau PET in CAA-ri has been rarely investigated. Method: We retrospectively described two cases of CAA-ri . We provided the temporal change of amyloid and tau PET in the first case, and the cross-sectional finding of amyloid and tau PET in the second case. We also performed a literature review of the imaging features of amyloid PET in reported cases of CAA-ri. Results: In the first case, an 88-year-old male presented with progressive consciousness and gait disturbances over two months. MRI showed disseminated cortical superficial siderosis. Amyloid PET prior to and after the CAA-ri revealed focally decreased amyloid load in the region of ARIA-E. In the second case, a 72-year-old male was initially suspected to have central nervous system cryptococcosis but later diagnosed with CAA-ri because of the characteristic MRI features and good response to corticosteroid treatment; a subsequent amyloid scan revealed positive amyloid deposition of the brain. Neither case suggested an association between the region of ARIA-E and higher amyloid uptake on PET before or after onset of CAA-ri. Our literature review revealed variable findings related to amyloid burden in post-inflammatory regions in previously reported CAA-ri cases with available amyloid PET. Our case is the first report of longitudinal changes on amyloid PET and show focal decreases in amyloid load after the inflammatory process. Conclusion: This case series highlights the need to better explore the potential of longitudinal amyloid PET in the understanding of the mechanisms of CAA-ri.